Modeled temperatures and fluid source distributions for the Mexican subduction zone: Effects of hydrothermal circulation and implications for plate boundary seismic processes. (26th February 2016) - Perry, Matthew; Spinelli, Glenn A.; Wada, Ikuko; He, Jiangheng
Abstract: In subduction zones, spatial variations in pore fluid pressure are hypothesized to control the sliding behavior of the plate boundary fault. The pressure‐temperature paths for subducting material control the distributions of dehydration reactions, a primary control on the pore fluid pressure distribution. Thus, constraining subduction zone temperatures are required to understand the seismic processes along the plate interface. We present thermal models for three margin‐perpendicular transects in the Mexican subduction zone. We examine the potential thermal effects of vigorous fluid circulation in a high‐permeability aquifer within the basaltic basement of the oceanic crust and compare the results with models that invoke extremely high pore fluid pressures to reduce frictional heating along the megathrust. We combine thermal model results with petrological models to determine the spatial distribution of fluid release from the subducting slab and compare dewatering locations with the locations of seismicity, nonvolcanic tremor, slow‐slip events, and low‐frequency earthquakes. Simulations including hydrothermal circulation are most consistent with surface heat flux measurements. Hydrothermal circulation has a maximum cooling effect of 180°C. Hydrothermally cooled crust carries water deeper into the subduction zone; fluid release distributions in these models are most consistent with existing geophysical data. Our models predict focused fluid release, which could generate overpressures, coincident with an observed ultraslow layer (USL) and a region of nonvolcanic tremor. Landward of USLs, a downdip decrease in fluid source magnitude could result in the dissipation in overpressure in the oceanic crust without requiring a downdip increase in fault zone permeability, as posited in previous studies. Key Points: Temperatures in the Mexican subduction zone are affected by fluid circulation in the oceanic crust Focused slab dehydration occurs in regions of slow slip, tremor, and ultraslow layers (USLs) A downdip decrease in dewatering rate can reduce overpressure without increasing fault permeability